Andragogy-Based Learning Planning: Study of Lecturer and Student Lecture Contract Models Islamic Education Study Program - Rahmat Rifai Lubis; Muhammad Ali Hanafiah; Nana Mahrani; Darwis Margolang (STAI Serdang Lubuk Pakam, 2022)
This study aims to analyze the application of andragogy aspects by lecturers to lecture contracts with students for one semester or commonly known as semester learning plans. The focus of the study is on 2 things, namely the form of andragogy aspects and andragogy-based learning planning as a lecture contract. The research method used is qualitative with a descriptive study based approach. Data collection techniques used are observation, interviews, and documentation studies. The data obtained was then analyzed using the Miles and Huberman technique, namely data reduction, data display, and drawing conclusions. The results of the study explained that according to the lecturers in the Islamic Cultural History Learning Strategy course, the andragogy aspect is very influential in the development of student learning. In addition, the lecture contracts for lecturers and students in the realm of the Faculty of Tarbiyah, State Islamic University of North Sumatra, have been adjusted and appropriate to be carried out with an agreement between the lecturers. and students. Through the lecture contract the lecturer can evaluate the final grade of the student, from these results it will be seen the development of student learning during one semester.